The Non-Linear Effect of Relative Real Foreign Exchange Rates on International Tourism Demand in Turkey: A Panel Threshold Modeling Approach - Huseyni, Ibrahim; Tunc, Ahmet; Celik, Ali Kemal (Int Journal Contemporary Economics & Administrative Sciences, 2022)
This paper aims to investigate (i) whether there is a certain threshold level that changes the effect of the relative real effective exchange rate on demand for tourism and, (ii) whether the volatility of the relative real effective exchange rate has an impact on demand for international tourism considering the non-linear relationship between the ratio of Turkey's real effective exchange rate to the real effective exchange rates of 29 OECD countries and the demand for international tourism in Turkey. Empirical results suggest that the real effective exchange rate has a threshold on demand for international tourism. Further, the relative real effective exchange rate volatility generating uncertainty has a significant and negative effect on demand for international tourism.
Keywords: Dynamic Panel Threshold Model; International Tourism Demand; Exchange Rate Volatility; Uncertainty; Turkey